COMPARISON OGIP (ORIGINAL GAS IN PLACE) ESTIMATION METHOD RESERVOIR GAS âXâ WITH SUBSIDENCE PROBLEM - SILABAN, MEITA
Subsidence or Surface Collapse is caused by the hydrocarbon exploitation in reservoir. This could happen in reservoir with big porosity and thickness. This study is trying to compare OGIP Estimation Methods that already exist and have been used in oil and gas industry for gas reservoir “X” with subsidence problem. Those Methods are volumetric, material balance, type curve (Blasingame and Agarwal-Gardner), Ramagost-Farshad Method and BlasingameRonald Gunawan Method. Since this reservoir has big porosity and thickness so when the hydrocarbon fluid produced, pore collapse takes place and by the overburden pressure formation rock is compressed and the reservoir volume is not constant anymore. The Result of OGIP Estimation between the method that counts rock compressibility and does not count the rock compressibility has big difference.